In vitro comparison of antimicrobial effects of colchicine and calcium hydroxide on salivary normal flora and five microbial strains - Behnaz Barekatain; Ali Reza Farhad; Poorandokht Refaei; Fariba Heidari (Isfahan University of Medical Sciences, 2011)
Introduction: Resistant microbial strains are major factors involved in root canal treatment failure. The aim of this study was to compare the antimicrobial properties of different concentrations of colchicine and calcium hydroxide. Materials and Methods: In this in vitro study, suspensions containing 5×105 colony-forming units of E. coli, E. faecalis, P. aeuroginosa, S. aureus, normal salivary flora and C. albicans and different concentrations (1, 0.5, 0.25, 0.125 and 0.0625 mg/mL) of calcium hydroxide and colchicine were prepared. The samples were incubated at 37°C for 24 hours. Then turbidity of the samples was evaluated to determine minimum inhibitory concentration (MIC). Then 0.1 mL of the broth with no turbidity was cultured on solid medium to determine minimum bactericidal concentration (MBC). In order to make sure of the accuracy of the process, positive, negative and standard controls were also prepared. Results: In evaluation of sample turbidity after 24 hours, all the tubes containing calcium hydroxide and positive controls showed complete turbidity. In tubes containing colchicine turbidity was found in all the bacterial categories. Only tubes containing Candida albicans with concentrations of 1, 0.5 and 0.25 mg/mL of colchicine were clear and lower concentrations showed turbidity. In evaluation of formation of colonies on Sab. Dextrose agar, only plates with 1 mg/mL of colchicine showed no growth.Conclusion: Only concentrations of 0.5 and 0.25 mg/mL of colchicine exhibited inhibitory effects and 1 mg/mL exhibited lethal effect on Candida albicans. None of the two drugs exhibited any inhibitory or lethal effects on other microbial strains. Key words: Antibacterial, Calcium hydroxide, Colchicine, Minimum bactericidal concentration, Minimum inhibitory concentration.